Metal man - Reynolds, Aaron, 1970-; Hoppe, Paul (Watertown, Mass. : Charlesbridge, 2010)
One hot summer day, a man who makes sculpture out of junk helps a boy create what he sees in his minds eye.
edited hb 2015-06-16
Keywords: African Americans -- Juvenile fiction; Children's stories; Creation (Literary, artistic, etc.) -- Pictorial works -- Juvenile fiction; Junk sculpture -- Juvenile fiction; Metal sculpture -- Pictorial works -- Juvenile fiction; Metal-work -- Juvenile fiction; Welding -- Pictorial works -- Juvenile fiction